2005
DOI: 10.1093/nar/gki534
|View full text |Cite
|
Sign up to set email alerts
|

Independent binding sites of small protein B onto transfer-messenger RNA during trans-translation

Abstract: Stalled bacterial ribosomes are freed by transfer-messenger RNA (tmRNA). With the help of small protein B (SmpB), protein synthesis restarts and tmRNA adds a tag to the stalled protein for destruction. The conformation of a 347 nt long tmRNA from a thermophile and its interactions with SmpB were monitored using structural probes. The RNA is highly folded, including the reading frame, with <30% of unpaired residues. Footprints between SmpB and tmRNA are in the elbow of the tRNA domain, in some pseudoknots inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 27 publications
4
25
1
Order By: Relevance
“…This result is in line with the recent SmpB protection study (Nameki et al 2005), but as many as three SmpB binding sites on tmRNA have been identified in another report (Metzinger et al 2005). One possible explanation for this apparent discrepancy is that putative, weak binding sites outside the TLD of tmRNA (Metzinger et al 2005) could have escaped detection in our lead-cleavage study.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This result is in line with the recent SmpB protection study (Nameki et al 2005), but as many as three SmpB binding sites on tmRNA have been identified in another report (Metzinger et al 2005). One possible explanation for this apparent discrepancy is that putative, weak binding sites outside the TLD of tmRNA (Metzinger et al 2005) could have escaped detection in our lead-cleavage study.…”
Section: Discussionsupporting
confidence: 88%
“…It includes nucleotides G333-C335 and U16-U17 in the TLD seen to interact with SmpB in the SmpB d TLD crystal structure from A. aeolicus (Gutmann et al 2003). The location of this footprint agrees with the suggestion that nucleotides 16-20 and 334-335 in the acceptor stem of the TLD have functional interactions with SmpB (Barends et al 2001;Wower et al 2002;Metzinger et al 2005) and the ribosome (Hanawa-Suetsugu et al 2001). No additional SmpB protections were seen when SmpB was present at a large molar excess over tmRNA (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…This emphasizes the functional significance of the interaction between tmRNA and SmpB presented here. Metzinger et al (2005) have shown that more than one molecule of SmpB from A. aeolicus binds to a tmRNA using surface plasmon resonance. The present study demonstrated that the interaction between the upstream region and SmpB depended on that between TLD and SmpB, although the total number of E. coli SmpB binding to one tmRNA is yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Functional interaction of SmpB with tmRNA www.rnajournal.org 1725 been shown in Aquifex aeolicus tmRNA by a chemical and enzymatic footprinting study (Metzinger et al 2005), although it has not yet been detected in E. coli tmRNA by studies of cross-linking or probing with lead(II) (Barends et al 2001;Wower et al 2002;Ivanova et al 2007). Protection was also found at G 14 , U 16 , U 17 , and G 19 in TLD.…”
Section: Interaction Of Smpb With the Upstream Region Of The Tag-encomentioning
confidence: 99%
“…Crystal structures of a complex between the TLD and SmpB provide a high-resolution view of the RNAprotein interaction, suggesting that SmpB acts as an anticodon mimic at the early steps of trans-translation (Gutmann et al 2003;Bessho et al 2007). The detailed structure of the remaining portion of the RNA relies on solution mapping (for a recent study performed on tmRNA from a thermophile, see Metzinger et al [2005]) combined with cryo-EM reconstructions of the RNA backbone, within the electron density of a preaccommodated ''tmRNA-SmpB-EF-Tu-70S'' complex (Kaur et al 2006).…”
Section: Introductionmentioning
confidence: 99%